Pengembangan model layanan profesional lonseling HIV/AIDS di provinsi Bali berbasis front-end analysis - Anak Agung Ngurah Adhiputra; Wayan Maba; Wery Dartiningsih (Indonesian Journal of Educational Development, 2020)
This study aims to analyze the development of a professional service model for HIV / Aids counseling in Bali province based on front-end analysis. The primary data of this research comes from literature studies, comparative studies, questionnaires, and field surveys. Using the sampling technique was selected purposively with the criteria for the development of status and region. The study used a sample of nine districts and cities in the province of Bali that have the Aids Commission (KPA). Learning development research is carried out by adopting 4D (Define, Design, Develop and Disseminate). The findings show comprehensive data on people infected with HIV / Aids by age, sex, and occupation at the national and provincial levels of Bali and designing a professional counseling service model for HIV / Aids based on front-end analysis and logically analyzed (expert judgment) through a panel group discussion. by experts for refinement. This research implies an increase in the performance and professionalism of the counselor and the client's response to changing risky behavior. Penelitian ini bertujuan untuk menganalisis pengembangan model layanan profesional konseling HIV/Aids di provinsi Bali berbasis front-end analysis. Data primer penelitian ini bersumber dari studi pustaka, studi komparasi, kuesioner, dan survey lapangan. Menggunakan teknik pengambilan sampel dipilih secara purposive dengan kriteria perkembangan status dan wilayah. Penelitian menggunakan sampel di sembilan kabupaten dan kota di provinsi Bali yang memiliki lembaga Komisi Penanggulangan Aids (KPA). Penelitian pengembangan pembelajaran dilakukan dengan mengadopsi 4D (Define, Design, Develop and Disseminate). Temuan menunjukkan data yang komprehensif orang terjangkit HIV/Aids berdasarkan usia, jenis kelamin, dan pekerjaan ditingkat nasional dan provinsi Bali serta merancang model layanan professional konseling HIV/Aids berbasis front-end analysis dan dianalisis secara logica (expert judgment) melalui sebuah panel group discussion oleh pakar untuk penyempurnaan. Penelitian ini memiliki implikasi adanya peningkatan kinerja dan professionalisme konselor dan respon dari klien untuk berubah perilaku berisiko.